Volumetric optoacoustic neurobehavioral tracking of epileptic seizures in freely-swimming zebrafish larvae - Özsoy, Çağla; Hotz, Adriana L.; Rieser, Nicolas N.; Chen, Zhenyue; Deán-Ben, Xosé Luís; Neuhauss, Stephan C. F.; Razansky, Daniel (Frontiers in Molecular Neuroscience, 2022)
Fast three-dimensional imaging of freely-swimming zebrafish is essential to understand the link between neuronal activity and behavioral changes during epileptic seizures. Studying the complex spatiotemporal patterns of neuronal activity at the whole-brain or -body level typically requires physical restraint, thus hindering the observation of unperturbed behavior. Here we report on real-time volumetric optoacoustic imaging of aberrant circular swimming activity and calcium transients in freely behaving zebrafish larvae, continuously covering their motion across an entire three-dimensional region. The high spatiotemporal resolution of the technique enables capturing ictal-like epileptic seizure events and quantifying their propagation speed, independently validated with simultaneous widefield fluorescence recordings. The work sets the stage for discerning functional interconnections between zebrafish behavior and neuronal activity for studying fundamental mechanisms of epilepsy and in vivo validation of treatment strategies.